O ROMANTISMO, NOSSO CONTEMPORÂNEO, EM AOS 7 E AOS 40, DE JOÃO ANZANELLO CARRASCOZA - JANAINA DOS SANTOS MIRANDA (2024)
The aim of this research is to carry out a critical reading and analysis of the novel entitled Aos 7 e aos 40 (2013), by João Anzanello Carrascoza. In order to verify and validate the presence of Romanticism as an aesthetic parameter and worldview in the literature produced by this contemporary author, who uses language and stylistic resources in order to emphasize the intimate context marked by the relationships between the subjects and at the same time position itself against the current of modern capitalist society. In this way, it is noted that Romanticism presents itself, in Carrascoze's production, through lyricism, subjectivity, freedom of creation and expression, escapism, figures of speech that are elements used by the author, to create an idealized environment that makes it possible to escape the values imposed by Modernity. Thus, in order to delve deeper into Romanticism, we took as a basis the theoretical texts entitled Revolta e Melancolia (2015), O Romantismo, Nosso Contemporâneo (1988), História Concisa da Literatura Brasileira (2022), in order to debate how the movement of Romanticism still shows itself in contemporary manifestations. Starting from the language, style and stylistic resources used by Carrascoza, who appropriates symbols, ellipsis, fragments, spaces and extended hyphens, themes such as memory, silence, the figure of the narrator and the short story genre are addressed. The research is based on theoretical assumptions by Bosi (2022), Candido (1988), D'Angelo (2006), Gagnebin (2009), Lausberg (1972), Löwy and Sayre (2015), Moisés (2010), Moisés (2008), Orlandi (2007), Reis (2018), Sartre (1999), Friedman (2002), Williams (1969). Keywords: Carrascoza. Romanticism. Brazilian Contemporary Literature. Stylistic Features